POLYTHROPIO MODEL OF THE COMPONENT OF CLOSE BINARY SYSTEM - Sirotkin, F. V. (Одеські астрономічні публікації, 2017)
In the present work we tried to resolve the problem about the detailed interior structure of the non-single star Which is the component of close binary system. We have consider the case of self-gravitation potential of the gaseous sphere, Which is influenced by the forces connected With rotation and tidal deformation from the companion. Considered models appear to be remarkably centrally condensed When compared With corresponding models of the non-rotating single stars. This circumstance can lead to some evolutionary changes in the close binary systems, Where one or two components